2440. Weight-Adjusted Piperacillin–Tazobactam (PIP/TAZ) Therapy in Obese Patients vs. Optimized Doses in Non-obese Patients: A Retrospective Cohort Study. (26th November 2018) - Moore, Sarah; Knoderer, Chad; Cheatham, S Christian
Abstract: Background: Dose optimized PIP/TAZ utilizing prolonged infusion has been shown to improve clinical outcomes. Previous pharmacokinetic studies of these prolonged infusion PIP/TAZ doses that achieve adequate time above minimum inhibitory concentration (T>MIC) in non-obese patients do not achieve similar concentrations in obese patients. Due to this higher doses are necessary in obese patients to achieve adequate T>MIC. Our institution utilizes weight-based dose optimization of PIP/TAZ in obese patients. The purpose of this study was to investigate clinical outcomes and adverse events with these dosing strategies compared with optimized doses in non-obese patients Methods: A retrospective single-center cohort study was conducted in patients ≥18 years old with culture-confirmed non-urinary tract Pseudomonas aeruginosa infections. Patients with positive cultures and PIP/TAZ treatment ≥24 hours were classified in groups as obese (≥120 kg) or non-obese (<120 kg). Results: 44 patients were studied in each arm with mean age 56 ± 13.8 and 65 ± 17.5, median weight 144 [132–170] and 77 [65–99] and median BMI 48 [40.5–56.2] and 26.4 [21.8–29.7] in the obese and non-obese groups respectively. Outcomes in obese compared with non-obese included composite clinical cure/improvement 86.4% and 77.2%, length of stay 8 and 10 days, ICU length of stay 10 and 8 days, hospital mortality 9.1% and 11.3%, 30 day mortality 15.9% and 18.2%, respectively. Adverse events in obese and non-obese groups occurred at 34.1% and 27.3% including AKI at 27% and 16% and thrombocytopenia at 7.1% and 12.8%, respectively. PIP/TAZ was discontinued due to safety concerns in 1 obese patient and 2 non-obese patients. Conclusion: Weight-adjusted PIP/TAZ doses in obese patients produce similar clinical outcomes to optimized doses in non-obese patients. Disclosures: All authors: No reported disclosures.